LEGAL IMPACT OF STATE DEFENSE ON INDONESIAN CITIZEN IN INTERNATIONAL HUMANITARIAN LAW PRESPECTIVE - Bunga, Gerald Aldytia; Tukan, Elisabeth Nirmalasari Bota (Yustisia, 2019)
Implementation of state defense in Indonesia can be implemented in military and non-military. Civilians can also be involved in state defense including in thoseconducted militarily, therefore this study is aimed at examining how national lawarrangements regulate the involvement of civilians in state defense which may beinvolved in military defense and how international humanitarian law regulates theinvolvement of civilians. This research uses normative legal research. The result ofthe research shows that involvement of civilians in military state defense can affectthem losing the protection they should enjoy in armed conflict.